Normalizace rusistiky na Filozofické fakultě Univerzity Karlovy - Tomáš Glanc (Slovo a Smysl, 2020)
This study draws on archival documents to trace the concrete implementation of ‘normalisation processes’ in Czechoslovak society, research fields, and the university during the 1970s and 1980s, focusing on the field of Russian studies in the Charles University Faculty of Arts. What makes this case of particular interest is the story of a Russianist at Charles University who studied the languages and cultures of countries whose leadership had decided to send military forces to participate in the occupation of Czechoslovakia. Writing on events through her perspective (a student at the time), the author examines in particular the environment of the late 1980s. In terms of methodology, the study combines witness accounts with a more thorough and intensive approach to evaluating the impact of normalisation on the field before and after November 1989.